Phase I clinical trial of cell therapy in patients with advanced chronic obstructive pulmonary disease: follow-up of up to 3 years - Stessuk, Talita; Ruiz, Milton Artur; Greco, Oswaldo Tadeu; Bilaqui, Aldemir; Ribeiro-Paes, Maria José de Oliveira; Ribeiro-Paes, João Tadeu [UNESP] (Associação Brasileira de Hematologia e Hemoterapia e daSociedade Brasileira de Transplante de Medula Óssea, 2013)
BACKGROUND Chronic obstructive pulmonary disease is a major inflammatory disease of the airways and an enormous therapeutic challenge. Within the spectrum of chronic obstructive pulmonary disease, pulmonary emphysema is characterized by the destruction of the alveolar walls with an increase in the air spaces distal to the terminal bronchioles but without significant pulmonary fibrosis. Therapeutic options are limited and palliative since they are unable to promote morphological and functional regeneration of the alveolar tissue. In this context, new therapeutic approaches, such as cell therapy with adult stem cells, are being evaluated.OBJECTIVE This article aims to describe the follow-up of up to 3 years after the beginning of a phase I clinical trial and discuss the spirometry parameters achieved by patients with advanced pulmonary emphysema treated with bone marrow mononuclear cells.METHODS Four patients with advanced pulmonary emphysema were submitted to autologous infusion of bone marrow mononuclear cells. Follow-ups were performed by spirometry up to 3 years after the procedure.RESULTS The results showed that autologous cell therapy in patients having chronic obstructive pulmonary disease is a safe procedure and free of adverse effects. There was an improvement in laboratory parameters (spirometry) and a slowing down in the process of pathological degeneration. Also, patients reported improvements in the clinical condition and quality of life.CONCLUSIONS Despite being in the initial stage and in spite of the small sample, the results of the clinical protocol of cell therapy in advanced pulmonary emphysema as proposed in this study, open new therapeutic perspectives in chronic obstructive pulmonary disease. It is worth emphasizing that this study corresponds to the first study in the literature that reports a change in the natural history of pulmonary emphysema after the use of cell therapy with a pool of bone marrow mononuclear cells.
Keywords: Cell transplantation; Pulmonary disease, chronic obstructive; Pulmonary emphysema; Stem cells; Spirometry; Clinical trial, phase I